Contributions to the morphology and histology of the reproductive system of Glancus atlanticus Forster (Gastropoda : Opisthobranchia) - Van Rensburg, W (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1986.